Neuroinflammation in Ischemic Stroke: Focus on MicroRNA-mediated Polarization of Microglia - Lian, Lu; Zhang, Yunsha; Liu, Lu; Yang, Liji; Cai, Yichen; Zhang, Junping; Xu, Shixin (Frontiers in Molecular Neuroscience, 2021)
Ischemic stroke is one of the most common cause of death and disability worldwide. Neuroinflammation, as a major pathological event, involves in the process of ischemic injury and repair. In particular, microglia show a double-edge role in neuroinflammation. In the acute phase of stroke onset, M2 microglia are the dominant phenotype and protective for the neuronal cells, but followed by permanent M1 microglia contribute to prolonged inflammation and are detrimental to brain tissue. Emerging evidence points to the regulatory effect of microRNAs on microglia-associated inflammation. Thus, we briefly review the dynamic response of microglia after stroke and then stress how specific microRNAs affect the behavior of reactive microglia. Finally, we point out that microRNAs should be a novel therapeutic option to modulate neuroinflammation and improve the stroke outcomes.